2008
DOI: 10.1007/s00253-008-1355-z
|View full text |Cite
|
Sign up to set email alerts
|

Hide depilation and feather disintegration studies with keratinolytic serine protease from a novel Bacillus subtilis isolate

Abstract: Keratinases play an important role in biotechnological applications such as improvement of feather meal, enzymatic dehairing and production of amino acids or peptides from high molecular weight substrates. Bacillus subtilis P13, isolated from Vajreshwari hot spring (45-50 degrees C) near Mumbai, India, produces a neutral serine protease and has an optimum temperature of 65 degrees C. This enzyme preparation was keratinolytic in nature and could disintegrate whole chicken feathers, except for the remnants of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 31 publications
4
53
1
Order By: Relevance
“…These include those reported by Gupta et al, (1999) and Haddar et al, (2009). Bleach stability was also attained through protein engineering (Pillai and Archana, 2008;Radha and Gunasekaran, 2008). These findings suggest the potential strong candidacy of SAPB and KERAB for application as cleaning additives in detergent formulations to facilitate the release of proteinacious materials in tough stains caused by blood, chocolate, grime, milk, etc.…”
Section: Potential and Prospects For Sapb And Kerab In Detergent Formsupporting
confidence: 64%
“…These include those reported by Gupta et al, (1999) and Haddar et al, (2009). Bleach stability was also attained through protein engineering (Pillai and Archana, 2008;Radha and Gunasekaran, 2008). These findings suggest the potential strong candidacy of SAPB and KERAB for application as cleaning additives in detergent formulations to facilitate the release of proteinacious materials in tough stains caused by blood, chocolate, grime, milk, etc.…”
Section: Potential and Prospects For Sapb And Kerab In Detergent Formsupporting
confidence: 64%
“…Moreover, because the β-sheet structure of amyloid prion proteins (PrP Sc ) is very similar to that of β-keratin in feathers, feather-degrading microorganisms and keratinases are recognized as potential degraders of the causative agents of transmissible spongiform encephalopathy (Langeveld et al 2003;Suzuki et al 2006;Yoshioka et al 2007). Other potential applications of keratinolytic microorganisms and keratinases include leather processing (Pillai and Archana 2008), the production of biodegradable films and keratin composites (Barone et al 2005), increasing ungual drug delivery (Mohorcic et al 2007), and biohydrogen generation from keratin-rich wastes (Bálint et al 2005;Brandelli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It can, therefore, be suggested that the commercial enzymes tested in this work presented some capability to digest the soft α-keratin. Pillai and Archana (2008) reported that an enzymatic preparation from Bacillus subtilis was ineffective in the hydrolysis of native α-keratin, while under similar conditions, the feather β-keratins were nearly completely degraded.…”
Section: Enzyme Application For Leather Unhairingmentioning
confidence: 99%